2010
DOI: 10.1088/0268-1242/26/2/025013
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependence of energy relaxation time in AlGaAs/GaAs heterojunctions: direct measurements

Abstract: We present measurements of the energy relaxation time, τ ε , of electrons in a single AlGaAs/GaAs heterojunction in a quasi-equilibrium state using microwave time-resolved spectroscopy at 4.2 K. We find the relaxation time has a power-law dependence on the carrier density of the two-dimensional electron gas, τ ε ∝ n γ s with γ = 0.40 ± 0.02 for values of the carrier density, n s , from 1.6 × 10 11 to 6.6 × 10 11 cm −2 . The results are in good agreement with predictions taking into account the scattering of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Thus, the conclusion is confirmed about the dominant role of the piezoelectric scattering in the non-elastic scattering processes in a single GaAs/AlGaAs heterojunction in the temperature region T = 1.6-5 K given by authors of [11,13]. Moreover, once more the evidence of the piezoelectric scattering in these structures at T = 4.2 K is given in [24]. The authors identified piezoelectric scattering as the leading energy relaxation mechanism in the BG regime on the grounds of the excellent agreement between experimental and calculated concentration dependences on the energy relaxation time of electrons in a single GaAs/AlGaAs heterojunction.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…Thus, the conclusion is confirmed about the dominant role of the piezoelectric scattering in the non-elastic scattering processes in a single GaAs/AlGaAs heterojunction in the temperature region T = 1.6-5 K given by authors of [11,13]. Moreover, once more the evidence of the piezoelectric scattering in these structures at T = 4.2 K is given in [24]. The authors identified piezoelectric scattering as the leading energy relaxation mechanism in the BG regime on the grounds of the excellent agreement between experimental and calculated concentration dependences on the energy relaxation time of electrons in a single GaAs/AlGaAs heterojunction.…”
Section: Resultssupporting
confidence: 70%
“…Such dependence was observed experimentally in the range of the 2DEG concentration n s = (1.6-6.6) × 10 11 cm −2 . Additionally, the measured dependence of the energy relaxation time on the dissipated dc power allows the authors of [24] to identify unambiguously the leading mechanism of energy relaxation as piezoelectric scattering.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations